Unfinished Business : Screening the Italian Mafia in the New Millennium - Renga, Dana, 1971- (Book collections on Project MUSE., 2013)
Unfinished Business argues that trauma that has yet to be worked through on the national level is displaced onto the characters in the films under consideration. In a mafia context, female characters are sacrificed and non-normative sexual identities are suppressed in order to solidify traditional modes of viewer identification and to assure narrative closure, all so that the image of the nation is left unblemished."--Pub. desc